PSYCHO-PEDAGOGICAL ASPECTS OF THE INTRODUCTION OF THE RELATIONSHIP BETWEEN SUPERIORS AND SUBORDINATES IN THE ARMED FORCES OF UKRAINE BASED ON EUROPEAN VALUES OF HUMAN RIGHTS - Дорохов, М. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article reveals the contents of certain documents of the Organization for Security and Cooperation in Europe (OSCE) on human rights and freedoms, including the servicemen of European countries. The aspects of the introduction of European standards of relationships between superiors and subordinates in the Armed Forces of Ukraine in accordance with European values of human rights and freedoms have been considered. Keywords: servicemen, western culture relations, European values, superior – subordinate, rights and freedoms.